1999
DOI: 10.1017/s0033291799008909
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences in alcohol sensitivity and the inheritance of alcoholism risk

Abstract: Background. Substantial evidence exists for an important genetic contribution to alcohol dependence risk in women and men. It has been suggested that genetically determined differences in alcohol sensitivity may represent one pathway by which an increase in alcohol dependence risk occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
207
1
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(218 citation statements)
references
References 46 publications
9
207
1
1
Order By: Relevance
“…A similar finding was obtained by observation of very rapid drinking results in an oral alcohol challenge protocol, although at later time points with falling BACs, the FHP subjects tended to demonstrate lower LRs than the FHNs . Second, supporting the probable reliability and validity of a low LR are data from all four relevant longitudinal studies showing that this phenotype predicts future heavier drinking and alcohol-related problems, with data generated in the United States, Australia, and Denmark (Heath et al, 1999;Rodriguez et al, 1993;Smith, 1996, 2000;Volavka et al, 1996). When used as part of an alcohol challenge protocol, the LR measures appear reliable as the correlation between two different doses of alcohol over several weeks is as high at .70, with a test-retest correlation at the same dose as high as .60 (Schuckit and Gold, 1988;Schuckit, 1985;Viken et al, 2003).…”
Section: Introductionmentioning
confidence: 78%
“…A similar finding was obtained by observation of very rapid drinking results in an oral alcohol challenge protocol, although at later time points with falling BACs, the FHP subjects tended to demonstrate lower LRs than the FHNs . Second, supporting the probable reliability and validity of a low LR are data from all four relevant longitudinal studies showing that this phenotype predicts future heavier drinking and alcohol-related problems, with data generated in the United States, Australia, and Denmark (Heath et al, 1999;Rodriguez et al, 1993;Smith, 1996, 2000;Volavka et al, 1996). When used as part of an alcohol challenge protocol, the LR measures appear reliable as the correlation between two different doses of alcohol over several weeks is as high at .70, with a test-retest correlation at the same dose as high as .60 (Schuckit and Gold, 1988;Schuckit, 1985;Viken et al, 2003).…”
Section: Introductionmentioning
confidence: 78%
“…Although some studies have found that the ADH1B*2 allele is associated with a lower rate of alcohol dependence (Tanaka et al, 1996;Wall et al, 2005b;Whitfield, 1997), others have not (Luczak et al, 2004;Takeshita et al, 1994). Furthermore, some alcohol challenge studies have found significant associations between ADH1B and level of response to alcohol Duranceaux et al, 2006), but others have not (Heath et al, 1999;Peng et al, 2002). Thus, prior data do not consistently support the hypothesis that ADH1B*2 leads to decreased rates of alcohol dependence via a more intense response to alcohol, and any such relationship may be further obscured when level of response to alcohol is assessed using self-report.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are homozygous for ALDH2*2 have been shown to have severe reactions to moderate doses of alcohol, including tachycardia, hypotension, nausea, and vomiting (Wall et al, 1992). Moreover, individuals with the most intense reactions to alcohol may not volunteer for alcohol challenge studies, resulting in participation bias (Heath et al, 1999). …”
mentioning
confidence: 99%
“…One behavioral characteristic related to this risk is a low level of response to an acute alcohol challenge (Schuckit, 1998), a trait that carries a similar estimated heritability of 40-60% (Schuckit and Smith, 1996;Heath et al, 1999). Linkage studies have identified regions on chromosomes 10, 11, 13, and 20 with LOD scores X3.0 that may contain genes that contribute to the level of response to alcohol (Schuckit et al, 2004).…”
Section: Introductionmentioning
confidence: 99%